Relationship between fiber & cholesterol intake, physical activity and nutritional status with blood glucose of Prolanis participants of Kedaton Health Center in 2024 - Nugroho, Arie; Wahyuni, Endang Sri; Sutrio, Sutrio; Pratiwi, Amali Rica; Yunianto, Andi Eka (Science Midwifery, 2024)
Diabetes mellitus is a metabolic disorder characterized by increased fasting blood glucose. The purpose of this studyto analyze the relationship between nutrient intake, nutritional status and physical activity with blood sugar levels. This research design usescross-sectionalwith a total of 42 respondents. Data on fiber and cholesterol intake usingSQ FFQ. Waist circumference data measured with a measuring tape with an accuracy of 0.1 cm and physical activity data measured using the Physical Activity Scale for the Elderly (PASE). Fasting blood glucose levels were measured using hexokinase. There was a significant relationship between fiber intake (p=0.001), cholesterol intake (p=0.006), and physical activity (0.014) to the increase in fasting blood glucose. However, waist circumference did not have a significant relationship to the increase in fasting blood glucose (p=0.895). Increased blood glucose was related to fiber intake, cholesterol intake, and physical activity, while waist circumference was not significantly related in the prolanis participants of Kedaton Health Center.